A 3D cone beam computed tomography (CBCT) investigation of mandibular condyle morphometry: Gender determination, disparities, asymmetry assessment and relationship with mandibular size - Mohammad Khursheed Alam; Kiran Kumar Ganji; Manay Srinivas Munisekhar; Nawaf Saleh Alanazi; Hussain Naif Alsharif; Azhar Iqbal; Santosh Patil; Nafij Bin Jamayet; Mohammed Sghaireen (Elsevier, 2021)
Objective: CBCT (cone beam computed tomography) analysis of condyle morphometry, to investigate the gender differences, symmetry and relationship with mandibular size. Materials and methods: This is a retrospective study. 800 CBCT scan obtained for the measurement of condyle in anterior-posterior and medio-lateral aspect using OnDemand 3D software. Participants were Saudi nationals of age above 18 years. 395 Males and 405 Females with the mean age of 38.2 ± 10.5 years. Right and left anterior-posterior width and medio-lateral width of the condyle were measured. Condyles were not isolated on the CBCT for volume measurement. Results: Mean right and anterior-posterior condyle width was 9.02 mm and 8.74 mm in males whereas in females it was 9.01 mm 8.69 mm respectively. For males mean medio-lateral width of the condyle in right and left side was 17.40 mm and 16.95 mm. For females, mean medio-lateral width of the condyle in right and left side was 17.14 mm and 16.93 mm. The prediction rate of gender was 57.2% for males and 53.3% for females. Statistically significant differences (p < 0.05) were found in the anterior-posterior and medio-lateral width of right and left condyles among males and females. Left anterior-posterior and medio-lateral width of average vs small mandible shows statistically significant difference (p < 0.05). Conclusion: Condyle morphometry is a weak predictor for gender. Irrespective of gender, right and left condyle are asymmetrical in relation to condyle morphometry of anterior-posterior and medio-lateral aspect. Left mandibular condyle morphometry is different in relation to the mandible size.